Understanding Charter School Leaders' Perceptions of Competition in Arizona. (December 2021) - Creed, Benjamin; Jabbar, Huriya; Scott, Michael
Purpose: School choice policies are expected to generate competition leading to improvement in school practices. However, little is known about how competition operates in public education—particularly in charter schools. This paper examines charter-school leaders' competitive perception formation and the actions taken in response to competition.Research Methods: Using Arizona charter-school leaders' responses to an original survey, Arizona Department of Education data, and the Common Core of Data, we examined the factors predicting the labeling of a school as a competitor. We estimated fixed effects logistic regression models which examine factors predicting the labeling of competitor schools and of top competitors. We used logistic regression models to understand charter-school leaders' responses to competition.Findings: We find charter-school leaders in Arizona perceived at least some competition with other schools, and their perceptions vary by urbanicity. While distance between schools mattered generally for labeling a school as a competitor, distance did not factor into labeling "top competitor" schools. Student outcomes did not predict competition between schools, but student demographics were associated with labeling a school a competitor. Charter-school leaders responded to competition through changes in outreach and advertising rather than curriculum and instruction. Competitive responses were related to the respondent school's quality and the level of perceived competition.Implications for Research and Practice: We found charter-school leaders perceive competition and respond by changing school practices. Responses typically focus on marketing activities over productive responses. The novel state-level analysis allows us to test the effects of local market conditions typically absent in the literature.